Pengembangan Media Web Interaktif (Mathventure) Berbasis Google Sites untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Materi Perkalian Kelas III SD - Ari Gunawan; Dani Kusuma (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to develop an interactive web learning media called Mathventure based on Google Sites, with a focus on improving the math problem solving skills of third grade elementary school students in multiplication material. The background of this research is driven by students' low understanding of the concept of multiplication and the lack of interesting and contextual learning media. The approach used in this research is the Research and Development (R&D) method with the ADDIE model involving five stages: analysis, design, development, implementation, and evaluation. The resulting product has been validated by material and media experts with excellent results. The pilot test was conducted in two elementary schools involving pretest, posttest, and student response questionnaire. The test results showed a significant increase in problem solving ability, with an N-Gain value of 0.6612, and a practicality level of 82%. This media is considered effective in creating learning that is fun, interactive, and able to motivate students in understanding the concept of multiplication. The implication of this research shows that web-based digital media can be an innovative solution to overcome math learning difficulties in elementary schools and has the potential to be further developed for other materials and levels.